2017
DOI: 10.5059/yukigoseikyokaishi.75.1179
|View full text |Cite
|
Sign up to set email alerts
|

Phosphole <i>P</i>-Oxide-Containing π-Electron Materials: Synthesis and Applications in Fluorescence Imaging

Abstract: Abstract:Phosphole P oxide is a useful building block for π conjugated materials due to its nonaromatic and electron accepting character. We have synthesized a series of ring fused derivatives of phosphole P oxide based on the intramolecular nucleophilic cyclization of appropriate alkyne precursors or radical phosphanylations. Some of the thus obtained compounds exhibited intriguing uorescence properties and were applied to uorescence imaging. A donor acceptor type benzo [b]phosphole P oxide with a (diphenylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…The components of S TDM also suggest that CBF-S has lower anisotropy in its shape (low λ S and S LX~0 .23), which is the main reason for the low S TDM , similarly to the cases found on CP2 and CBM. Originally, the phenyl group attached to the phosphorus has been designed and required because of the synthetic reason, ie, availability of the starting materials and the stability toward the reaction conditions 39,47,48 . Here it is theoretically suggested that the structural nature, ie, >P(=O)Ph, also plays an important role in realising negative fluorescence anisotropy of phosphole oxide-based dyes in the present NLCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The components of S TDM also suggest that CBF-S has lower anisotropy in its shape (low λ S and S LX~0 .23), which is the main reason for the low S TDM , similarly to the cases found on CP2 and CBM. Originally, the phenyl group attached to the phosphorus has been designed and required because of the synthetic reason, ie, availability of the starting materials and the stability toward the reaction conditions 39,47,48 . Here it is theoretically suggested that the structural nature, ie, >P(=O)Ph, also plays an important role in realising negative fluorescence anisotropy of phosphole oxide-based dyes in the present NLCs.…”
Section: Resultsmentioning
confidence: 99%
“…Five phosphole oxide-based fluorescent dyes (racemic mixtures)-(CP2), (CBM), (CBX), (CBF) and (CNX) (Fig. 2b)-were synthesised according to previously reported methods 39,[46][47][48] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Previously,w er eportedt he synthesis of as eries of phosphole-based p systems and studied their suitability for bioimaging by capitalizing on the electron-accepting character of the phosphole P-oxide. [19] By combining the electron-accepting benzophosphole P-oxide with an electron-donating triphenylamine moiety,w ed eveloped an environment-polarity-sensitive fluorescent probe,L ipiDye ( Figure 1a). [20] This donor-p-acceptor-type( D-p-A) probe exhibited high photostability, which was further increased by reinforcing the 2-arylbenzophosphole P-oxide skeleton with am ethylene bridge (C-Bphox;F igure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported the synthesis of a series of phosphole‐based π systems and studied their suitability for bioimaging by capitalizing on the electron‐accepting character of the phosphole P ‐oxide . By combining the electron‐accepting benzophosphole P ‐oxide with an electron‐donating triphenylamine moiety, we developed an environment‐polarity‐sensitive fluorescent probe, LipiDye (Figure a) .…”
Section: Introductionmentioning
confidence: 99%